Pengaruh Sistem Pengukuran Kinerja dan Sistem Penghargaan terhadap Keefektifan Penerapan Teknik Total Quality Management Studi Empiris pada Perusahaan Manufaktur di Indonesia - Retno Kurnianingsih; Nur Indriantoro (The Indonesian Journal of Accounting Research, 2013)
Studies examining the manufacturing practices using Total Quality Management (TQM) and the management accounting system designs that  interactively affected performance became an interesting area of research for many years. TQM was a technique that was frequently used by  manufacturing companies in order to improve the company’s effectiveness through performace. The management accounting system designs used in this study were performance measurement system and the reward system as the moderating variables.Data of the study was collected via mail survey to managers. This study used 47 respondens of managers from various functional departments of manufacturing companies listed in the capital market directory 1999. Data was analyzed using multiple regression model. Further analysis showed that there were positive effects of the TQM techniques as well as the performance measurement system and reward system on the managerial performance. The results of this study supported previous studies’ finding that high performance can be achieved if the TQM manufacturing practices were employed along with the moderating variables, i.e. the performance measurement system and reward system.